Surface roughness and colour changes of nanofilled composite resin after immersion in yogurt drink - Sindy Widyaningrum; Purwanto Agustiono; Harsini Harsini (Majalah Kedokteran Gigi Indonesia, 2020)
Nanofilled composite resin is one of restorative materials with some weaknesses, such as changes of colour and surface roughness. These weaknesses are attributed to some factors, including frequent consumption some beverages, including yoghurt drinks. This study aims to determine the effect of long immersion of nanofilled composite resin in guava yogurt drink on discoloration and changes in surface roughness. Subjects of the study were nanofilled composite resin materials (3M Filtek Z350XT shade A3) in cylindrical shape with a diameter of 10 mm and 2 mm thickness. Study was conducted by immersing nanofilled resin composites in 10 mL of guava yogurt drink at 37 °C. Twelve specimens were divided into 3 groups with immersion duration of 12 hours, 24 hours, and 36 hours. Surface roughness measurements were carried out using a profilometer Starrett SR300 surface roughness tester, while the colour measurement parameters according to the system L * a * b * was measured using chromameter Konica Minolta CR-400 before and after treatment. Data of changes in surface roughness and colour changes data (ΔE) were calculated and analysed using one-way ANOVA. The results showed insignificant surface roughness changes but significant colour changes in nanofilled composite resin in the groups of 12 hours, 24 hours, and 36 hours. It is concluded that immersion duration in guava yoghurt drink significantly affects the colour of nanofilled composite resin.